Effect of soapy water on the behavior of semiaquatic hemipterans (Gerromorpha) from two neotropical aquatic ecosystems - Arias-Paco, Andrés; Mata-Nuñez, Melanie; Alvarado-Barrantes, Ricardo (Revista de Biología Tropical, 2021)
Introduction: Semiaquatic hemipterans are insects that may be among the best indicators of the quality of the aquatic environment, specifically in terms of the content of substances that break surface tension. However, no studies are evaluating how these insects are affected by changes in the surface tension of the water. Objective: To determine the effect of soapy water on the locomotion ability of three species of neotropical semiaquatic hemipterans. Methods: From August to November 2020, we conducted ex situ experiments, with nine groups of ten individuals of the family Veliidae (N = 90) and Gerridae (N = 90), where each group individually, was subjected to the entry of soapy water for three minutes. For this, we designed an aquarium consisting of three plastic boxes at different heights, connected to each other, so that a current flow was generated. We used powdered laundry soap, liquid hand soap, and bar soap for dishes. For each type of soap we prepared a low (9 ppm), medium (50 ppm) and high (200 ppm) concentration. By means of recordings, we recorded the time the hemipterans spent in the water, as well as their ability to get out of the water, and whether or not they sank. Results: We found that, regardless of the type of soap, the time spent by hemipterans in contaminated water decreases drastically as the concentration increases, but the impact varies by species, with Rhagovelia solida (family Veliidae) being less affected by pollution compared to Platygerris caeruleus and Potamobates unidentatus (family Gerridae). Conclusions: The use of these taxa as indicators of the degree of contamination of rivers by detergents and soaps can be very useful, especially if we take into account the differences in sensitivity according to the family or gender of the group.